Pengaruh Model Experiential Learning Berbantuan Media Gambar Powerpoint Terhadap Keterampilan Menulis Puisi Siswa Kelas VIII SMP Plus Darussalam Blokagung - Badriyah, Siti Lailatul; Hikmah, Siti Nur Afifatul (Lembaga Intelektual Muda (LIM) Maluku, 2023)
The aim of this research is to determine the influence of the experiential learning model assisted by PowerPoint image media on the poetry writing skills of class VIII students at SMP Plus Darussalam and to find out how much influence the experiential learning model assisted by PowerPoint image media has on the poetry writing skills of class VIII students at SMP Plus Darussalam. This research uses quantitative research methods with experimental research type. The data collection technique in this research is by using a questionnaire. The sample used was 60 students. The research results from the T-test showed that count> table, namely 25.679 > 2.000, which means Ho is rejected and Ha is accepted. So, it can be concluded that the independent variable (X) of the experiential learning model has a significant influence on poetry writing skills. The experiential learning model has a large influence on poetry writing skills, namely 91.9%, the remaining 8.1% is influenced by other variables. So, it can be concluded that there is an influence in the use of the experiential learning model assisted by PowerPoint image media on the poetry writing skills of class VII students at SMP Plus Darussalam